PENGARUH LATIHAN SMALL SIDED GAMES DAN LATIHAN RONDO TERHADAP KETEPATAN PASSING PADA PEMAIN KLUB FUTSAL ALDIFA BANJARMASIN - Fitrian, Zanzabil Adwa (Journal of Sport and Exercise Science, 2022)
This study was conducted to determine the effect of the Small Sided Games (SSG) and Rondo exercises on the accuracy of passing on the players of the Futsal club Aldifa Banjarmasin. The experimental method used in this research is the "Two Group Pre-test and Post-test Design" research design. The sample in this study amounted to 20 people with a sampling technique using purposive sampling technique. The treatment grouping was done using MSOP (Match Subject Ordinal Pairing). The research instrument used the development of a test instrument to measure football ability which was adopted from DR. Norbert Rogalski and DR. Ernst Dagel. Data analysis in this study used prerequisite tests which included normality and homogeneity tests. The data obtained from the initial test and final test of graduation accuracy that have gone through the prerequisite test stage are followed by hypothesis testing using the t-test. The value of the SSG group hypothesis test was obtained (6,678 > 2,262), while the rondo group hypothesis test was obtained (2,372 > 2,262). Thus from these results prove that there is a significant effect of each of these exercises. The results of the t-test were obtained (1.310 < 2.101), thus the results of the t-test showed that there was no significant difference between the two groups. However, if it is seen from the number of differences in the average posttest of the group where the SSG is 6.80 while Rondo is 5.90, so it has a difference of 0.900 which is higher in the SSG group. So these results prove that the two training methods in this study have the same effect, but the SSG group has a better effect in terms of passing accuracy compared to Rondo training on Aldifa Banjarmasin futsal club players.